Horizontal product differentiation, pollution abatement and emission taxes under Cournot oligopoly. - Gautier, Luis (Nova Science Publishers, 2015)
There is an increasing number of firms across a variety of industries, which are taking steps to differentiate themselves as environmentally conscious firms, both to achieve gains from product differentiation and to reduce production and pollution abatement costs. In light of this trend in many industries, this chapter considers a horizontally differentiated Cournot model to examine (i) the role of pollution abatement efforts by firms on the characterization of the optimal emission tax and (ii) the adjustment of optimal policy as products become differentiated. The analysis indicates that in the presence of abatement efforts by firms the government may afford a tax reduction to address the output distortion as products become more differentiated. Additionally, the analysis suggests that policies which may encourage firms to differentiate themselves as environmentally conscious firms may aid in the reduction of industry emissions, and at the same time allow a reduction in the emission tax to address the output distortion present in imperfectly competitive markets.
Política de acceso abierto tomada de: https://novapublishers.com/wp-content/uploads/2023/02/FAQ-Authors-Rights-Copy-2.pdf y https://novapublishers.com/open-access/
Keywords: Contaminación - Reducción; Impuestos ambientales; Política ambiental; Cournot; Emission taxes; Horizontal product differentiation; Environmental policy